Synthesis of FSO2-Functionalized Oxindoles via a Radical Fluorosulfonylation/Intramolecular Arylation Cascade - Yang, Na; Pei, Guanhua; Li, Hao; Han, Junwei; Wang, Peng; Xie, Lili; Liao, Saihu (Synthesis, 2024)
Herein, we report the development of a FSO2 radical initiated tandem cyclization reaction under visible light photoredox catalysis, which allows for a facile access to FSO2-functionalized oxindoles from N-arylacrylamides. This reaction features mild reaction conditions, readily available starting materials, and SuFExable products. The introduction of sulfonyl fluoride groups into oxindoles could be of interest for related study in the context of discovering new bioactive molecules.
Keywords: FSO2 radicals; photoredox catalysis; oxindoles; SuFEx; click chemistry